Removal of tetracycline antibiotic by Lemna gibba L. from aqueous solutions - Topal, Murat; Obek, Erdal; Uslu Senel, Gulsad; Arslan Topal, E. Isil (Wiley, 2020)
In this study, the efficiency of Lemna gibba L. on tetracycline (TC) removal from the solutions prepared at various initial TC concentrations (50, 100 and 300 mu g/L) was investigated. The study was conducted in the reactors planted with Lemna gibba L. plants. Lemna gibba L. plants in the reactors were harvested at various hydraulic retention times. Then, the concentrations of TC were determined by using LC/-MS-MS. The maximum removal efficiencies for the TC50, TC100 and TC300 in the planted reactors were 99.8 +/- 4.1; 99.9 +/- 4.9 and 99 +/- 4.9%, respectively. The harvesting times for Lemna gibba L. at TC50, TC100 and TC300 concentrations were determined to be 12, 8 and 12 hours, respectively. First-, second- and pseudo-first-order kinetics are determined in the planted reactors (with Lemna gibba L.). According to the study results, second-order kinetics were obtained at TC50, TC100, TC300 concentrations. As a result, the Lemna gibba L. plant can be used as an alternative treatment method to other advanced treatment methods and it can be done with a cheap method by adapting to existing treatment plants. Lemna gibba L. plants can be used to remove pollutants by applying them to polluted lakes and water bodies.
Keywords: kinetic; Lemna gibba L; removal; tetracycline